1995
DOI: 10.1161/01.cir.91.5.1461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Chamber Localization, and Subtype Distribution of Angiotensin II Receptors in Human Hearts

Abstract: Angiotensin II receptors in human myocardium are present in relatively low numbers, and AT2 is the predominant subtype. A significant loss of angiotensin II receptors occurs in end stage but not in moderate heart failure. The loss of receptors affects both subtypes to a comparable degree. The data suggest that the decrease in receptor density is due to a decrease in steady-state mRNA abundance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(80 citation statements)
references
References 32 publications
6
71
0
3
Order By: Relevance
“…Total Ang II receptor numbers in LV were in the range of 3.8 to 17.3 fmol/mg protein (Table), similar to the results reported by the previous studies, [13][14][15][16] but were lower than the receptor numbers (118, nϭ5) determined by de Gasparo et al 17,37,38 de Gasparo et al used combined fractions including plasma membranes and internalized receptors, whereas we and other studies [13][14][15][16] measured Ang II receptor numbers using only membrane fractions. In fact, Regitz-Zagrosek et al 14 found that the B max values determined with combined fractions were increased compared with those using only membranes.…”
Section: Discussionsupporting
confidence: 89%
“…Total Ang II receptor numbers in LV were in the range of 3.8 to 17.3 fmol/mg protein (Table), similar to the results reported by the previous studies, [13][14][15][16] but were lower than the receptor numbers (118, nϭ5) determined by de Gasparo et al 17,37,38 de Gasparo et al used combined fractions including plasma membranes and internalized receptors, whereas we and other studies [13][14][15][16] measured Ang II receptor numbers using only membrane fractions. In fact, Regitz-Zagrosek et al 14 found that the B max values determined with combined fractions were increased compared with those using only membranes.…”
Section: Discussionsupporting
confidence: 89%
“…There are very few data on AT 2 R or its blockade because AT 2 R was considered to be in low abundance, without significant functional consequences (28). The two distinct subtypes of ANG II receptors were identified on the basis of their inhibition by highly specific and selective nonpeptide ANG II receptor ligands, losartan for AT 1 R and PD-123319 for AT 2 R (6, 29).…”
Section: Discussionmentioning
confidence: 99%
“…This concept (16,17,33) assumes that during chronic AT 1 R blockade, shunting of ANG II to AT 2 Rs induces AT 2 R activation and unopposed AT 2 R effects involving bradykinin, PGs, and NO, but data on AT 2 R protein or mRNA or downstream signaling are needed. Under chronic conditions, AT 2 Rs in coronary endothelial cells exert antigrowth and antiproliferative effects that are offset by the growthpromoting effects of AT 1 R stimulation (28). AT 2 Rs also mediate apoptosis (38), so that AT 2 R blockade could inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Так-же установлено, что при сочетанном действии изопротеренола и ингибиторов ренин-ангиотен-зиновой системы устраняется не только эффект повышения концентрации ангиотензина II, но и нормализуется масса левого желудочка, а также снижается выраженность фиброзных изменений миокарда [40]. В дополнение к этому следует от-метить, что рецепторы ангиотензина II выявлены в сердце различных млекопитающих, включая чело-века [41], и их стимуляция увеличивает продукцию коллагена фибробластами сердца, а также стиму-лирует белковый синтез и развитие гипертрофии кардиомиоцитов [42]. Другими словами, действие ангиотензина II приводит к тем же принципиаль-ным структурным изменениям миокарда, что на-блюдаются при хронической активации симпати-ческой нервной системы.…”
Section: роль ренин-ангиотензиновой системыunclassified